From Women Fitrah to Space: Exploring Islamic Value on Womanhood in Architecture and Design - Putri, Aida Nur Afiyah Alfi; Handryant, Aisyah Nur (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
The challenges faced by women today, particularly in education, skill development, and protection from domestic violence (DV), underscore the need for architectural solutions that address their unique needs. This study aims to explore how Islamic perspectives on women’s roles as individuals, mothers, daughters, and educators can be integrated into the design of a Women Hub. The significance of this research lies in its potential to provide inclusive, safe, and empowering spaces for women, particularly in Kediri, a region experiencing a significant rise in domestic violence cases. The research employs a descriptive-exploratory methodology, utilizing qualitative data analysis and literature review to propose architectural solutions rooted in Islamic values. Data collection involves examining relevant cultural, social, and architectural frameworks that align with the principles of dignity, respect, and balance in Islam. The findings demonstrate that aligning spatial design with women’s intrinsic roles and needs can effectively address social inequalities, promote community engagement, and support personal and collective development. The study concludes that architecture can serve as a powerful medium for fostering women’s empowerment while maintaining harmony with Islamic principles. Practical implications of this research include the design of women-centered spaces that prioritize safety, education, and personal growth, ultimately contributing to a more equitable and supportive societal structure.